A Human Endogenous Retrovirus Suppresses Translation of an Associated Fusion Transcript, PLA2L - Kowalski, Paul E. (American Society for Microbiology, 1998)
Human endogenous retroviruses (HERVs) are repetitive, noninfectious chromosomal elements degenerated from exogenous retroviruses. The HERV-H family is composed of approximately 1,000 elements which are dispersed throughout the human genome. We have shown previously that an HERV-H element splices into a downstream locus, termed PLA2L, which has a large open reading frame (ORF) containing two domains with phospholipase A2 homology. Over half of the putative 5′ untranslated region (5′ UTR) of the resulting fusion transcript is derived from HERV-H long-terminal-repeat and internal sequences. As 5′ UTRs are known to modulate translation initiation, we tested for possible effects upon gene expression at the translation level due to the 5′ fusion with HERV-H sequences. No PLA2L protein was detected in teratocarcinoma cell lines in which PLA2L mRNA is abundantly expressed. In addition, despite a high level of transcription, no protein synthesis was detected when the full-length PLA2L cDNA was expressed in COS cells. Upon removal of the 5′-terminal HERV-H sequences, PLA2L protein was seen in transfectants. The 5′ UTR contains both small ORFs and a strong predicted RNA secondary structure, both of which have been shown to contribute to translation suppression. The HERV-H sequences, combined with a unique PLA2L 5′ UTR sequence, form a predicted RNA stem-loop that has a stability greater than that proposed to negatively affect translation. Interestingly, this stem-loop is abolished when the HERV-H sequences are removed. We hypothesize that the PLA2L 5′ HERV-H sequences function as an abnormally long and complex 5′ UTR, resulting in suppression of translation in both teratocarcinoma cell lines and full-length cDNA transfectants. This is the first known example of a endogenous retrovirus integration affecting expression of a heterologous human gene at the translational level.